2018
DOI: 10.1136/vetreccr-2017-000532
|View full text |Cite
|
Sign up to set email alerts
|

Polypoid cystitis in a male entire springer spaniel puppy

Abstract: A 14-week-old entire male springer spaniel was presented for haematuria. Investigations identified polypoid cystitis. Medical management failed to improve the clinical signs, and the dog underwent surgical excision of the bladder polyps at eight months old. Histopathological examination of the polyps identified granulomatous foci containing crystalline material. Eighteen months after surgery, the dog has had no further episode of haematuria and repeat ultrasound-documented resolution of the lesions. This is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The shape of the polyps is also thought to favor urine retention and bacterial adhesion to the mucosa, instigating a vicious cycle of infection-proliferation-inflammation. 3,11 While canine polypoid cystitis typically occurs in adult dogs, Ruiz et al 8 reported the occurrence of the disease in a 14-week-old springer spaniel puppy that presented due to recurrent hematuria. In that previous case, bacterial urine culture was negative, however, urinalysis intermittently revealed the presence of struvite crystals.…”
mentioning
confidence: 99%
“…The shape of the polyps is also thought to favor urine retention and bacterial adhesion to the mucosa, instigating a vicious cycle of infection-proliferation-inflammation. 3,11 While canine polypoid cystitis typically occurs in adult dogs, Ruiz et al 8 reported the occurrence of the disease in a 14-week-old springer spaniel puppy that presented due to recurrent hematuria. In that previous case, bacterial urine culture was negative, however, urinalysis intermittently revealed the presence of struvite crystals.…”
mentioning
confidence: 99%